CD30 Is Dispensable for T-Cell Responses to Influenza Virus and Lymphocytic Choriomeningitis Virus Clone 13 but Contributes to Age-Associated T-Cell Expansion in Mice - Zhou, Angela C.; Snell, Laura M.; Wortzman, Michael E.; Watts, Tania H. (Frontiers in Immunology, 2017)
CD30 is a tumor necrosis factor receptor (TNFR) family member whose expression is associated with Hodgkin’s disease, anaplastic large cell lymphomas, and other T and B lymphoproliferative disorders in humans. A limited number of studies have assessed the physiological role of CD30/CD30 ligand interactions in control of infection in mice. Here we assess the role of CD30 in T cell immunity to acute influenza and chronic lymphocytic choriomeningitis virus (LCMV) clone 13 infection, two viral infections in which other members of the TNFR superfamily are important for T cell responses. We show that CD30 is expressed on activated but not resting CD4 and CD8 T cells in vitro, as well as on regulatory T cells and marginally on Th1 cells in vivo during influenza infection. Despite this, CD4 and CD8 T cell expansion in response to influenza virus was comparable in CD30+/+ and CD30-/- littermates, with no discernable role for the pathway in the outcome of influenza infection. Similarly, during persistent infection with LCMV clone 13, CD30 plays no obvious role in CD4 or CD8 T cell responses, the level of T cell exhaustion or viral control. On the other hand, in the steady state, we observed increased numbers of total CD4 and CD8 T cells as well as increased numbers of regulatory T cells in unimmunized older ( 8 months) CD30+/+, but not in CD30-/- age-matched littermates. Naïve T cell numbers were unchanged in the aged CD30+/+ mice compared to their CD30-/- littermate controls, rather the T cell expansions were explained by an increase in CD4+ and CD8+ CD44mid-hiCD62L- effector memory cells, with a similar trend in central memory T cell compartment. In contrast, CD30 did not impact the numbers of T cells in young mice. These data suggest a role for CD30 in the homeostatic regulation of T cells during aging, contributing to memory T cell expansions which may have relevance for CD30 expression in human T cell lymphoproliferative diseases.